Short-term delay in neural response with multifocal contact lens might start at the retinal level - Fernandes, Paulo (2022)
Introduction Multifocal simultaneous imaging challenges the visual system to process the multiple overlaps of focused and defocused images. Retinal image processing may be an important step in neuroadaptation to multifocal optical images. Our aims are, firstly to evaluate the short-term effect of different multifocal contact lenses (MF) on retinal activity in young healthy subjects (Experiment#1) and secondly, to evaluate any changes in retinal activity in presbyopic patients fitted with MF over a 15-day period (Experiment#2). Methods In Experiment-#1, 10 emmetropic healthy young subjects were included to evaluate the short-term effect of different MFs designs. In Experiment #2, 4 presbyopic subjects were included to wear MF for 15 days. Following the ISCEV Standards, multifocal electroretinograms (mfERGs) were recorded to evaluate different retinal regions under different conditions: with single vision contact lens (SVCL) and with center-distance and center-near MF. Results In Exp#1 the peak time of N1, P1 and N2 were found to be delayed with the MF (p <= 0.040). There was a significant reduction for N1 amplitude in all retinal regions (p < 0.001), while for P1 and N2 amplitudes this reduction was more significant in the peripheral regions (p < 0.005, ring 5 to 6). With center-near MF the mean response density (nV/deg(2)) showed a significant decrease in all wave components of the mfERGs response, particularly from Ring 3 to Ring 6 (p < 0.001, all Rings). In Exp#2, the mean mfERG response is similar between SVCL and center-distance MF, while center-near MF showed an increase in implicit time N1 and P1 on day 1 that tends to recover to baseline values after 15 days of MF wear. Conclusions significant changes in the mfERGs responses were found with the MF lens, being most noticeable with the center-near MF lens design. The present results suggest that the observed delay in cortical response described during the adaptation to multifocality may partially begin at the retina level.